2021
DOI: 10.1039/d1en00497b
|View full text |Cite
|
Sign up to set email alerts
|

Release of gold (Au), silver (Ag) and cerium dioxide (CeO2) nanoparticles from sewage sludge incineration ash

Abstract: Conservative engineered nanoparticles (ENPs) that resist transformation during wastewater treatment and sludge incineration can be released from sewage sludge ash. Transient ENPs that undergo transformation are retained in the sewage sludge ash.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…NMs that transform into other (nanoparticulate) chemical species. 53,55 But considering how these NMs transform during their real-world applications (e.g. combustion in diesel engines), this study shows that CeO 2 NMs may be more persistent than expected even during anaerobic digestion.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…NMs that transform into other (nanoparticulate) chemical species. 53,55 But considering how these NMs transform during their real-world applications (e.g. combustion in diesel engines), this study shows that CeO 2 NMs may be more persistent than expected even during anaerobic digestion.…”
Section: Discussionmentioning
confidence: 76%
“…more resistant to transformation in managed waste facilities) due to their enhanced chemical stability acquired during combustion. 55 At the low concentration of aged NMs used during AS production (spiked concentrations of comb-CeO 2 -NMs of 130 μg L −1 ), all the physico-chemical and biological proxies showed that comb-CeO 2 NMs neither altered the AS microbial community structure nor the C, P, N removal capacity. However, the presence of 99.9% of the total CeO 2 injected (without change in speciation) in the AS biosolids altered the production, structure, and activity of the anaerobic sludge during AD (impacting the EPS, ATP, lipase and α-glucosidase activities).…”
Section: Discussionmentioning
confidence: 91%
“…Nonetheless, silver particles are expected to accumulate over time in environmental compartments (Gottschalk et al, 2013), especially with continual application of the nanomaterial source. Metallic silver nanoparticles (Ag-NP) in consumer products have sizes that range between 10 and 100 nm (Kaegi et al, 2011;Tulve et al, 2015;Wielinski et al, 2021), which are smaller than the microspheres used in our experiments. This modification in concentration and particle size from expected values of sludge-receiving soils was required for visualization of deposited material with XCT, as described in Section 2.3.…”
Section: Methodsmentioning
confidence: 99%
“…Suspensions of 20 g L −1 were prepared in the desired background aqueous solution (described below) and used in experiments within 10 hr. Concentrations of metallic silver in waste water are usually below 5 mg L −1 (Wielinski et al., 2021). Nonetheless, silver particles are expected to accumulate over time in environmental compartments (Gottschalk et al., 2013), especially with continual application of the nanomaterial source.…”
Section: Methodsmentioning
confidence: 99%
“…So far, very little has been published regarding the release of nanoparticles from SSA. In a very recent study, Wielinski et al [ 8 ] investigated the release of different nanomaterials from SSA in column experiments, but the column experiments described therein are very different to the standard column elution used for evaluation of source strength in the scope of regulation. Further, laboratory column experiments need references from the “real world” to assess the robustness of the laboratory results.…”
Section: Introductionmentioning
confidence: 99%